Endoscopy Novel Techniques and Recent Advancements - Teodor Streba, Costin; Ionut Gheonea, Dan; Constantin Vere, Cristin (IntechOpen, 2019)
Endoscopic techniques are widely used for screening, diagnostic and therapeutic maneuvers in all groups of patients and for a large spectrum of complaints. The availability of basic iterations of endoscopic techniques made screening programs for various diseases viable in most parts of the world, while the advent of modern techniques opens new perspectives for rapid and correct diagnosis. Going beyond normal human vision, innovative techniques opened the prospect of in-situ pathology. Endoscopic ultrasound has made incredible progress in recent years. Reaching the smaller orifices by endoscopy was a major step forward in the surveillance of previously inaccessible lesions. Investigatory techniques were complemented by advances in therapy, with novel applications in many major areas of medicine.